Global SUMOylation facilitates the multimodal neuroprotection afforded by quercetin against the deleterious effects of oxygen/glucose deprivation and the restoration of oxygen/glucose. Issue 1 (6th June 2016) - Lee, Yang‐ja; Bernstock, Joshua D.; Nagaraja, Nandakumar; Ko, Brian; Hallenbeck, John M.
Abstract : Quercetin acts to increase survival in the face of ischemia via an increase of SENP3 expression, the possible inactivation of SENPs 1/2, and via a decrease in KEAP1 levels (thereby increasing Nrf2 stability). These changes may then lead to increase in HIF‐1α SUMOylation and HO‐1 activation, followed by an up‐regulation of NOS1/PKG signaling. Pathways altered via quercetin treatment within our experimental system are represented by blue arrowheads. Solid black arrows represent relationships that have been explored while a dotted arrow represents a relationship that has yet to be confirmed. Abstract: The putative neuroprotective properties of various flavonoids have long been reported. Among this class of chemicals, quercetin, a major flavone/flavonol naturally occurring in plants, deserves focused attention because of the myriad of beneficial effects observed in various in vitro and in vivo models of central nervous system damage/degeneration. However, the mechanisms governing the beneficial outcomes mediated by quercetin remain to be elucidated. In an effort to define the underlying molecular mechanisms, our study employed human/rat neuroblastoma cell lines (SHSY5Y and B35, respectively) and E18‐derived rat primary cortical neurons upon which the effects of various flavonoids were examined. Of note, increases in the levels of global SUMOylation, a post‐translational modification with theS mallU biquitin‐likeMO difier (SUMO) were pronounced. Quercetin treatment increased SUMOylation levels in both SHSY5Y cells and rat cortical neurons in a dose and time‐dependent manner, possibly via the direct inactivation of certain SENPs (SUMO‐specific isopeptidases). Of particular interest, cells treated with quercetin displayed increased tolerance to oxygen/glucose deprivation exposure, an in vitro model of ischemia. SHSY5Y cells treated with quercetin also increased the expression of Nrf2 (via a decrease in the levels of Keap1), heme oxygenase‐1 (HO‐1), and nitric oxide synthase 1 (NOS1), which provide further protection from oxidative stress. In addition, the increased SUMOylation of HIF‐1α was noted and deemed to be significant. We hypothesize that SUMOylated HIF‐1α plays a fundamental role in the protection afforded and may underlie some of quercetin's ability to protect cells from oxygen/glucose deprivation‐induced cell death, via an up‐regulation of HO‐1 and NOS1, which ultimately leads to the induction of pro‐life NOS1/protein kinase G signaling. Quercetin acts to increase survival in the face of ischemia via an increase of SENP3 expression, the possible inactivation of SENPs 1/2, and via a decrease in KEAP1 levels (thereby increasing Nrf2 stability). These changes may then lead to increase in HIF‐1α SUMOylation and HO‐1 activation, followed by an up‐regulation of NOS1/PKG signaling. Pathways altered via quercetin treatment within our experimental system are represented by blue arrowheads. Solid black arrows represent relationships that have been explored while a dotted arrow represents a relationship that has yet to be confirmed.